Penguasaan Shiekibun Pada Mahasiswa Tahun Masuk 2017 Program Studi Pendidikan Bahasa Jepang Universitas Negeri Padang - Afrina Wati; Meira Anggia Putri (Universitas Negeri Padang, 2020)
Abstract This study discusses the mastery of Shiekibun in 2017 students of Japanese language study programs at Padang State University. The purpose of this study was to determine the Shiekibun mastery of 2017 students entering the Japanese Language Study Program at Padang State University. This type of research used in this research is quantitative research with descriptive methods. The population in this study were students entering 2017 Japanese Language Education Study Program, Padang State University, amounting to 56 people. The sample in this study amounted to 30 people. The data of this study are the Shiekibun mastery test scores for 2017 students entering the Japanese Language Study Program at Padang State University. Based on the results of the research carried out it can be concluded that the mastery of student Shiekibun in 2017 in general is in the qualification